Influence of defect states and fixed charges located at the a-Si:H/c-Si interface on the performance of HIT solar cells. (1st January 2017) - Oppong-Antwi, Louis; Huang, Shihua; Li, Qiannan; Chi, Dan; Meng, Xiuqing; He, Lv
Highlights: Efficiency of 29.19% in bifacial HIT solar cell was first achieved by simulation. Defect states and fixed charges at a-Si:H/p-Si interface were considered. Band bending dependent on interface defect states and fixed charges was confirmed. Abstract: In this work, a simulation study of various HIT solar cell structures was carried out using AFORS-HET simulation software. The effect of defect states and fixed charges at the a-Si:H/p-Si interface on the solar cell performance was investigated. We found that the defect states located at the upper side of the a-Si:H/p-c-Si interface affected the HIT performance more greatly than those located at the bottom side of the a-Si:H/p-c-Si interface. However, compared with interface defect states, interface fixed charges located on both sides of the c-Si wafer had an opposite effect. The crucial role of strong band bending in the crystalline part of the a-Si:H/c-p-Si interface was shown through the variation of interface defect states and interface fixed charges. By optimizing the densities of interface defect states and interface fixed charges, an efficiency of 29.19% was achieved.